Pulmonary Outcomes in Children Born Extremely and Very Preterm at 11 Years of Age - Di Filippo, Paola; Giannini, Cosimo; Attanasi, Marina; Dodi, Giulia; Scaparrotta, Alessandra; Petrosino, Marianna Immacolata; Di Pillo, Sabrina; Chiarelli, Francesco (Frontiers in Pediatrics, 2021)
Background: There is increasing evidence of prematurity being a risk factor for long-term respiratory outcomes regardless the presence of bronchopulmonary dysplasia (BPD). Aim: To assess the effect of prematurity on respiratory outcomes in children born ≤32 weeks of gestational age at 11 years of age. Materials and Methods: 55 ex-preterm children (≤ 32 weeks of gestational age), born in Chieti between 1st January 2006 and 31th December 2007, performed lung function and diffusing capacity test (DLCO) at 11 years of age. Furthermore, allergy evaluation by Skin Prick Test (SPT), eosinophil blood count and assessment of eosinophilic airways inflammation by exhaled nitric oxide (FeNO) were performed. The ex-preterm group was compared to an age- and sex-matched group of term children. Results: No difference for atopic and respiratory medical history was found between ex-preterm children and term controls, except for preschool wheezing that resulted more frequent in ex-preterm children. No difference neither in school-aged asthma frequency nor in lung function assessment at 11 years of age was found between the two groups. Lower DLCO values in ex-preterm children compared to term controls regardless the presence of BPD were found; furthermore, we showed a positive association between DLCO and gestational age. Eosinophil blood count, positive SPTs and FeNO values were similar between the two groups. Conclusions: Diffusing lung capacity was decreased in ex-preterm children at 11 years of age in the absence of lung function impairment and eosinophil airway inflammation, suggesting a non-eosinophilic pattern underlying pulmonary alterations. It could be desirable to include the diffusing capacity assessment in follow-up evaluation of all ex-preterm children.